Management Overview of the Lung Tuberculosis Control Program at the DKI Jakarta Provincial Health Office in 2023 - Kiranti, Mutiara; Andriani, Helen (Journal of Indonesian Health Policy and Administration, 2024)
Tuberculosis is one of the infectious diseases that is fatal if not cured immediately. In 2022, the success rate of tuberculosis treatment in DKI Jakarta Province is 81%, while the national target is 90%. In the field, the number of cadres to carry out contact investigations is still insufficient, so that in 2022 the coverage of contact investigations in DKI Jakarta Province will only reach 25%, while the national target is 90%. To increase the scope of successful treatment, the government should try to overcome tuberculosis, which is needed. Proper program management is required to run effectively and efficiently for tuberculosis control efforts. Therefore, this study aims to determine the management picture of tuberculosis control programs at the DKI Jakarta Provincial Health Office. This qualitative research type uses in-depth interview methods, observation, and document review. Determination of informants using purposive sampling techniques. Data validation using source triangulation by and method triangulation. The results showed that in the management of the tuberculosis control program, there are problems, including limited cadres to conduct contact investigations, limited recording and reporting personnel at health facilities, there are still health facilities carrying out TB diagnoses not according to standards, not yet integrated SITB with SITK, and still limited services for MDR-TB (multidrug-resistant tuberculosis). Suggestions that can be given are optimizing the role of cadres to conduct contact investigations, providing recording and reporting personnel in addition to nurses and personnel on duty in TB services at health facilities, disseminating the latest information to health facilities through socialization, immediately integrating SITB with SITK and coordinating with private health service facilities to open MDR-TB services.